DNR and COVID-19: The Ethical Dilemma and Suggested Solutions - Sultan, Hala; Mansour, Razan; Shamieh, Omar; Al-Tabba', Amal; Al-Hussaini, Maysa (Frontiers in Public Health, 2021)
Ethics are considered a basic aptitude in healthcare, and the capacity to handle ethical dilemmas in tough times calls for an adequate, responsible, and blame-free environment. While do-not-resuscitate (DNR) decisions are made in advance in certain medical situations, in particular in the setting of poor prognosis like in advanced oncology, the discussion of DNR in relation to acute medical conditions, the COVID-19 pandemic in this example, might impose ethical dilemmas to the patient and family, healthcare providers (HCPs) including physicians and nurses, and to the institution. The literature on DNR decisions in the more recent pandemics and outbreaks is scarce. DNR was only discussed amid the H1N1 influenza pandemic in 2009, with clear global recommendations. The unprecedented condition of the COVID-19 pandemic leaves healthcare systems worldwide confronting tough decisions. DNR has been implemented in some countries where the healthcare system is limited in capacity to admit, and thus intubating and resuscitating patients when needed is jeopardized. Some countries were forced to adopt a unilateral DNR policy for certain patient groups. Younger age was used as a discriminator in some, while general medical condition with anticipated good outcome was used in others. The ethical challenge of how to balance patient autonomy vs. beneficence, equality vs. equity, is a pressing concern. In the current difficult situation, when cases top 100 million globally and the death toll surges past 2.7 million, difficult decisions are to be made. Societal rather than individual benefits might prevail. Pre-hospital triaging of cases, engagement of other sectors including mental health specialists and religious scholars to support patients, families, and HCPs in the frontline might help in addressing the psychological stress these groups might encounter in addressing DNR in the current situation.